ChemInform Abstract: Coexistence of Monochalocogen and Dichalocogen Ions in BiSe2 and BiS2 Crystals Prepared at High Pressure. Issue 25 (5th June 2015) - Yamamoto, Ayako; Hashizume, Daisuke; Bahramy, Mohammad Saeed; Tokura, Yoshinori
Abstract: Single crystals of BiSe2 and BiS2 are prepared at 5.5 GPa (700—1100 °C) and characterized by single crystal XRD.